Methodology and reporting quality of 544 studies related to ageing: a continued discussion in setting priorities for ageing research in Africa - Michael E Kalu; Chukwuebuka Okeke; Ernest Nwachukwu; Augustine Okoh; Olayinka Akinrolie; Chigozie D Ezulike; Henrietha Adandom; Ogochukwu K Onyeso; Joesph Egbumike; Funmibi D Olatunji; Ebere P Ugwuodo; Blessing U Ojembe; et al. (International Society of Global Health, 2022)
# Background The quality assessment provides information on the overall strength of evidence and methodological quality of a research design, highlighting the level of confidence the reader should place on the findings for decision making. This paper aimed to assess the quality (methodology and quality of reporting) of ageing studies in Sub-Saharan Africa (SSA). # Method This paper is the second of a Four-Part Series paper of a previous systematic mapping review of peer-reviewed literature on ageing studies conducted in SSA. We updated the literature search to include additional 32 articles, a total of 544 articles included in this paper. Downs & Black checklist, Case Report guidelines checklist, the 45-items Lundgren et al. checklist, and the Mixed Method Appraisal Tool were used to assess the methodological quality of quantitative, case reports, qualitative, and mixed-method studies. Quality assessment was piloted and conducted in pairs for each study type. Depending on the checklist, each study was classified as excellent, good, fair, or poor. # Result Of the 544 articles, we performed the quality assessment of a total of 451 quantitative studies \[Randomized control trials (RCTs) and pre-post (n=15), longitudinal (n=122), case-control (n=15) and cross-sectional (n=300); 4 case reports, 74 qualitative and 15 mixed-method studies. Only 20.4% (n=111) articles were of high quality \[one RCT, 27 longitudinal, 4 case-control, 48 cross-sectional studies, 19 qualitative, and 12 mixed-method studies\]. The remaining 433 were rated as moderate quality (n=292, 53.7%), fair quality (n = 96, 17.7%) and poor quality (n = 45, 8.2%). Most (80%) quantitative articles' sample size is small, resulting in insufficient power to detect a clinically or significant important effect. Three-quarter (75%) of the qualitative studies did not report their research team characteristics and a reflexivity component of the 45-items Lundgren et al. checklist. Mixed-method studies with low quality did not report the qualitative studies properly. # Conclusion We conclude that the methodological and quality reporting of published studies on ageing in SSA show variable quality, albeit primarily moderate quality, against high quality. Studies with a large sample size are recommended, and qualitative researchers should provide a section on research team members' characteristics and reflexivity in their paper or as an appendix.